Global characterization of GH11 family xylanases genes in Neostagonosporella sichuanensis and functional analysis of Nsxyn1 and Nsxyn2 - Liu, Lijuan; Li, Chengsong; Liang, Fang; Han, Shan; Li, Shujiang; Yang, Chunlin; Liu, Yinggao (Frontiers in Microbiology, 2024)
Rhombic-spot disease, caused mainly by Neostagonosporella sichuanensis, significantly impacts the yield and quality of fishscale bamboo (Phyllostachys heteroclada). Xylanases are essential for pathogenic fungi infection, yet their specific functions in the physiology and pathogenicity of N. sichuanensis remain unclear. Here, we characterized three xylanase proteins with glycosyl hydrolase 11 domains from the N. sichuanensis SICAUCC 16–0001 genome and examined the function of Nsxyn1 and Nsxyn2. Purified Nsxyn1 and Nsxyn2 proteins displayed specific xylanase activity in vitro and induced cell death in Nicotiana benthamiana, independent of their enzymatic function. Both proteins possessed signal peptides and were confirmed as secreted proteins using a yeast secretion system. Subcellular localization revealed that Nsxyn1 and Nsxyn2 localized in both the cytoplasm and nucleus and can trigger cell death in N. benthamiana through Agrobacterium tumefaciens-mediated transient transformation. qRT-PCR results showed notable upregulation of Nsxyn1 and Nsxyn2 during infection, with Nsxyn1 exhibiting an 80-fold increase at 15 days post-inoculation. Deletion of Nsxyn1 and Nsxyn2 in N. sichuanensis impaired xylan degradation, adaptation to osmotic and oxidative stress, and pathogenic full virulence. Deletion of Nsxyn1 notably slowed fungal growth and reduced spore production, whereas only a reduction in microconidial production was observed in Nsxyn2 mutants. Complementation of Nsxyn1 and Nsxyn2 only partially restored these phenotypic defects in the ∆Nsxyn1 and ∆Nsxyn2 mutants. These findings suggest that Nsxyn1 and Nsxyn2 contribute to N. sichuanensis virulence and induced plant defense responses, providing new insights into the function of xylanases in the interaction between fishscale bamboo and N. sichuanensis.